No child left behind: Universal child care and children's long-run outcomes - Tarjei Havnes; Magne Mogstad (University of Oslo, Department of Economics, 2009)
There is a heated debate in the US, Canada and many European countries about introducing universally accessible child care. However, studies on universal child care and child development are scarce and only consider short-run outcomes. We analyze the introduction of universal child care in Norway, addressing the impact on children's long-run outcomes. Our precise and robust difference-in-difference estimates show that child care had strong positive effects on children's educational attainment and labor market participation, and also reduced welfare dependency. Subsample analysis indicates that children with low educated mothers and girls benefit the most from child care.
Keywords: J13; H40; I28; 330; universal child care; child development; long-run outcomes; Kinderbetreuung; Bildungsverhalten; Erwerbstätigkeit; Schätzung; Norwegen